On Coordinated Multi-Point Transmission for Cellular Environments - Silva, Mário Marques da (2014)
Current and emergent services are demanding higher data rates, improved spectral e±ciency and increased network capacity. To face these new requirements, it is important to ¯nd schemes able to reduce the e®ects of fading and to exploit new types of diversity. Coordinated Multi-Point transmission (CoMP) comprises the coordinated transmission of signals from adjacent base stations (BS), and the corresponding reception from user equipments (UE). CoMP transmission is an important technique that can mitigate inter-cell interference, improve the throughput, exploit diversity and, therefore, improve the spectrum e±ciency. This paper performs a comparison between di®erent multi-antenna techniques that can be employed in CoMP to achieve the requirements of the Fourth Generation Cellular Systems (4G).